TP53 mutation in patients with high‐risk acute myeloid leukaemia treated with allogeneic haematopoietic stem cell transplantation. (13th January 2016) - Middeke, Jan M.; Herold, Sylvia; Rücker‐Braun, Elke; Berdel, Wolfgang E.; Stelljes, Matthias; Kaufmann, Martin; Schäfer‐Eckart, Kerstin; Baldus, Claudia D.; Stuhlmann, Reingard; Ho, Anthony D.; Einsele, Hermann; Rösler, Wolf; et al.
Summary: Treatment success in patients with acute myeloid leukaemia (AML) is heterogeneous. Cytogenetic and molecular alterations are strong prognostic factors, which have been used to individualize treatment. Here, we studied the impact of TP53 mutations on the outcome of AML patients with adverse cytogenetic risk treated with allogeneic haematopoietic stem cell transplantation (HSCT). Samples of 97 patients with AML and adverse‐risk cytogenetics who had received a HSCT within three randomized trials were analysed. Complete sequencing of the TP53 coding region was performed using next generation sequencing. The median age was 51 years. Overall, TP53 mutations were found in 40 patients (41%). With a median follow up of 67 months, the three‐year probabilities of overall survival (OS) and event‐free survival for patients with TP53 wild type were 33% [95% confidence interval (CI), 21% to 45%] and 24% (95% CI, 13% to 35%) compared to 10% (95% CI, 0% to 19%) and 8% (95% CI, 0% to 16%) ( P = 0·002 and P = 0·007) for those with mutated TP53, respectively. In multivariate analysis, the TP53 ‐mutation status had a negative impact on OS (Hazard Ratio = 1·7; P = 0·066). Mutational analysis of TP53 might be an important additional tool to predict outcome after HSCT in patients with adverse karyotype AML.